The Relationship between Electric Vehicles and Smart Cities: A Literature Review - Wang, Yongguan (Transactions on Economics, Business and Management Research, 2024)
This literature review explores the interconnectedness of electric vehicles (EVs) and smart cities, focusing on sustainability and technological integration. The study examines infrastructure requirements, sustainable mobility applications, and the digital aspects of smart cities and EVs. It discusses the role of technologies like the Internet of Things (IoT) in facilitating EV integration, the implications of policy and economics on EV adoption, and the importance of urban planning and societal perspectives. The paper also highlights existing research gaps and the need for further exploration into the synergistic relationship between EVs and smart cities.